Science in history - Bernal, J. D (M.I.T. Press, 1954)
J. D. Bernal's monumental work Science in History is the first full-scale attempt to analyze the relationship between science and society throughout history, from the perfection of the first flint hand ax to the construction of the hydrogen bomb. This remarkable study illustrates the impetus given to and the limitations placed upon discovery and invention by pastoral, agricultural, feudal, capitalist, and socialist systems, and conversely the ways in which science has altered economic, social, and political beliefs and practices.In this final volume, Professor Bernal enters the disputed field of the social sciences and provides an avowedly Marxist outline of their history and of the social and political tendencies of our times. Drawing on conclusions from history, he discusses in a final chapter the future role of science in society.